UPAYA MEWUJUDKAN GERAKAN INDONESIA BERSATU SEBAGAI BENTUK GERAKAN REVOLUSI MENTAL DALAM PROSES PEMBELAJARAN IPS - Simatupang, Diorima; Kotrunida, Syelpia; Yuliana, Noviyanti; Arinata, Firdian Setiya; Khoerunnisa, Siti (Universitas Negeri Semarang, 2021)
Tolerance is one of the goals of the National Mental Revolution Movement, especially the United Indonesia Movement. The diversity of Indonesian people's backgrounds and the problems that often arise due to this diversity make the Indonesian government very serious in creating Indonesian people who are able to accept and respect this diversity and increase the character of tolerance among Indonesian people. The implementation of the United Indonesia Movement is also the responsibility of all levels of Indonesian society, especially educational institutions, in this case education is expected to be able to create generations of people who are able to live and respect all the diversity that exists. Social studies education is one of the efforts or forums that can facilitate the implementation of the United Indonesia Movement and create a tolerant society. . The plurality of materials contained in the content of social studies subject matter is one of the tangible forms used by educational institutions to implement and implement the United Indonesia Movement in the scope of education.